Systematic review on health care professionals’ competencies in the care of LGBT+ individuals - Willian Roger DULLIUS; Lara Barros MARTINS; Vanessa Monteiro CESNIK (Estudos de Psicologia (Campinas))
Abstract This review encompasses both national and international literature about training needs analyses for health care professionals working with the LGBT+ population. The descriptors “health professionals”, “health providers”, “LGBT”,“training needs analysis” were searched in the following databases: Academic OneFile, Academic Search Complete, Medical Literature Analysis and Retrieval System Online, Virtual Health Library, Cumulative Index to Nursing and AlliedHealth Literature, Complementary Index, Business Source Complete, Education Source, Gender Studies, National Center for Biotechnology Information, Scientifi c Electronic Library Online, SportDiscus, and PsycINFO. Inclusion criteria were:empirical articles, published from 2007 to 2017, in indexed and peer-reviewed journals, available in full text, in Portuguese or English versions. Of the 17 included articles, most were published in North American countries. There is a need for training and formal protocols within institutions. Training had positive results. No instruments about the competencies for health care professionals working with the LGBT+ population were identifi ed. Further studies should be conducted in the fi eld of health care professionals training to provide satisfactory health care services to this public.